Evaluasi Penerapan Sistem K3 Dalam Pembelajaran Praktek: Studi Kasus Pada Prodi Sarjana Terapan Teknik Listrik - Dodie, Stanley; Rumokoy, Stieven N.; Simanjuntak, Christopel H.; Wenno, Leony A.; Khasanah, Fata Nidaul (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
Occupational Safety and Health (OSH) is a crucial aspect of practical learning, especially in vocational education that focuses on technical skills. The Applied Bachelor’s Degree Program in Electrical Engineering at Manado State Polytechnic has a curriculum that involves various practical activities, including electrical and mechanical work. The risk of work accidents in this learning process is relatively high, making the effective implementation of an OSH system essential to creating a safe and conducive learning environment. This study was conducted in the Applied Bachelor’s Degree Program in Electrical Engineering at Manado State Polytechnic to evaluate the implementation of the OSH system in practical learning. The evaluation aims to identify aspects that need improvement or enhancement to minimize the risk of accidents and ensure compliance with applicable safety standards. The research methodology includes literature review and descriptive study. The literature review examines relevant OSH regulations and guidelines, while the descriptive study is carried out through observations and interviews with individuals involved in practical activities. The findings indicate that although the OSH system has been implemented, there are still aspects that need improvement, particularly in providing OSH facilities and equipment for working at heights. Observations reveal that the use of personal protective equipment (PPE), such as full-body harnesses and other supporting tools, has not been fully implemented in accordance with applicable safety standards. This evaluation can serve as a foundation for developing more effective policies to improve safety and the quality of practical learning in vocational education.